Setting the Research Agenda for Nursing Administration and Leadership Science: A Delphi Study. (September 2021) - Chipps, Esther Maria; Joseph, M. Lindell; Alexander, Catherine; Lyman, Bret; McGinty, Logan; Nelson-Brantley, Heather; Parchment, Joy; Rivera, Reynaldo R.; Schultz, Mary Anne; Ward, Danielle M.; Weaver, Susan
Abstract : OBJECTIVE: The aim of this study was to identify and prioritize research topics for nursing administration and leadership science. BACKGROUND: Nursing administration and leadership research priorities should provide a framework for building the science needed to inform practice. METHODS: The Association for Leadership Science in Nursing (ALSN) and American Organization for Nursing Leadership (AONL) Foundation (AONL-F) for Nursing Leadership and Education collaborated on a Delphi study. Initial input on research priority items were received from ALSN and AONL members. National experts participated in a 3-round Delphi study. RESULTS: Top-ranked priorities included: 1) nurses' health, well-being, resiliency, and safety in the workplace; 2) developing and managing a nursing workforce to meet current and future healthcare needs; 3) healthy work/practice environments for direct care nurses; 4) healthy work/ practice environments for nurse leaders; 5) quantification of nursing's value across the healthcare delivery system; and 6) nurse leader development and essential competencies. CONCLUSIONS: Researchers and funders should use these priorities to guide future studies.